Family Interpersonal Conflict in Inside Out Movie - Devin, Devin; Joni, I Dewa Ayu Sugiarica; Pradipta, Ade Devia; Damasemil, Calvin (E-Jurnal Medium, 2024)
Life and interactions between people have been depicted by various works such as movies. Since the 20th century, the development of movies has fostered great interest in society so that these developments have produced various genres, one of which is the animation genre. The animated film entitled "Inside Out" is one of the animated films produced by Disney/Pixar and has won the Academy Awards for the category "Best Animated Feature Film of the Year" in 2016. The film directed by Pete Docter also won 100 other awards and was named "Movie of the Year" by the AFI Awards in 2016. The victory for the work was basically born as a description of the social reality that was inspired based on his relationship with his daughter. The work was also adapted from a description of the social reality that often occurs between children who are in the puberty phase and their parents. Through the development of this film work, there are various psycholgical sides of children in puberty that have been explored together with a number of psychological scientists in order to develop a work that can describe the growth process of a person based on real life. Based on interpersonal communication theory, the research entitled "Family Interpersonal Conflict in Inside Out Movie" aims to identify how interpersonal communication conflicts occur in the family of RIley's character in the Inside Out animated film using descriptive qualitative research with a constructivist paradigm. Through sources obtained from the content of images and videos from the 95-minute Inside Out film, the findings in this film research found that there are nine scenes that can be categorized as interpersonal conflict situations and the forms of interpersonal conflicts in Inside Out films are divided into several types of interpersonal conflicts, namely pseudo-conflicts, fact conflicts, value conflicts, and policy conflicts. Keywords: Animated Film, Family, Inside Out, Interpersonal Conflict